70.3k views
0 votes
Composition Function

Use f(x) = x + 2 and g(x) = x2 - 2x

1)Evaluate f(g(-1))

Could you explain how to solve this problem?  ̄へ ̄

User Sefe
by
6.3k points

1 Answer

5 votes

well you find g(-1) which is g(-1) = (-1)^2 - 2(-1) = 3

then you shove thawt into f since g(-1)=3

so f(g(-1)) = f(3) = 3+2= 5

in other words f(x) = x + 2 and g(x) = x² - 2x have composition

f(g(x)) = (x² - 2x) + 2

remember in function notation, where ever you see x you replace

e.g. f(x) = x + 2,

f(2) = 2 + 2

f(3) = 3+2

f(x+y) = x+y+2

so f(g(-1)) = g(-1) + 2

User Ericmp
by
6.0k points